IDENTIFIKASI POTENSI BALE BANJAR SEBAGAI TEMPAT PENDIDIKAN IKLIM DI KALANGAN PEMUDA BALI MELALUI PENERAPAN TEORI CREATIVE PLACEMAKING - ADIARTHA, MADE ARYA; PRASANDYA, KM. DEDDY ENDRA (Ganec Swara, 2025)
This research explores the potential of the Bale Banjar as a space for climate education among Balinese youth through the application of Creative Placemaking. In the context of the increasingly urgent climate crisis, the Bale Banjar, functioning as a traditional community space, holds strategic value in bringing climate education closer to the everyday lives of Balinese youth. This study employs a mixed-method approach, involving a Likert-scale-based questionnaire and open-ended questions to collect data on youth perceptions of the Bale Banjar space. Based on the analysis, 94% of respondents indicated they would visit the Bale Banjar more frequently if improvements were made to the 10 identified criteria. By integrating elements of Creative Placemaking, the Bale Banjar can be more effectively utilized as a culturally relevant center for climate education and engagement. These findings provide recommendations for spatial improvements to enhance the comfort, accessibility, and educational function of the Bale Banjar. The results are expected to serve as a guide for future initiatives aiming to leverage community spaces for sustainable environmental education among younger generations